Traffic and QoS Management in Wireless Multimedia Networks COST 290 Final Report - Siris, Vasilios; Braun, Torsten; Barcelo-Arroyo, Francisco; Staehle, Dirk.; Giambene, Giovanni; Koucheryavy, Yevgeni; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
This book contains the description of the research work done in ESF COST 290 Action "Traffic and QoS Management in Wireless Multimedia Networks" which ran from March 2004 to June 2008. Twenty four European countries contributed to the research within the ESF COST 290 Action with more than 70 institutions involved. The authors address new techniques and approaches to deal with the growth of data traffic in wireless mobile networks and the important need to guarantee differentiated quality of service levels to different traffic classes. The material presents the latest research achievements and results in research areas such as traffic engineering, mobility and interoperability, network architectures and planning as well as services, regulations, and economic aspects. This book covers broad areas of research on wireless communications and networking from the physical layer through the application layer. It is recommended for researchers and PhD students to receive a comprehensive and up-to-date overview on engineering approaches, optimization methods and open issues in wireless multimedia networks.
The Research Agenda of the COST 290 -- Packet Scheduling and Congestion Control -- Performance Evaluation and Traffic Modeling -- Mobility Support -- Multihop Wireless Networks -- Services, Optimization, and Economic Aspects.
Keywords: ENGINEERING; COMPUTER NETWORK ARCHITECTURES; COMPUTER COMMUNICATION NETWORKS; INFORMATION SYSTEMS; COMPUTER ENGINEERING; TELECOMMUNICATION; ENGINEERING; COMMUNICATIONS ENGINEERING, NETWORKS; ELECTRICAL ENGINEERING; COMPUTER COMMUNICATION NETWORKS; COMPUTER SYSTEMS ORGANIZATION AND COMMUNICATION NETWORKS; INFORMATION SYSTEMS APPLICATIONS (INCL.INTERNET).